Eco-Friendly Packaging and Its Influence on Purchasing Decision Process - Petra KOUDELKOVÁ (Communications of International Proceedings, 2022)
Sustainability has been a phenomenon for several years. It is based on economic, social and environmental pillars. It is also crucial in the case of packaging management. Customers rarely want to buy products in eco-friendly packaging. The packaging could affect their purchasing decision. On the other hand, it also is influenced by many factors. The research paper aims to contribute to better understanding of motives for buying products in eco-friendly packaging. We examine what could influence the decision buying process. Here both qualitative (individual interviews) and quantitative (questionnaire) research methods were used. Results could be used in marketing or management practice.
Keywords: eco-friendly packaging; packaging material; purchasing decision process; black box